Event-triggered model predictive control for grid-connected three-phase inverter. (4th April 2022) - Chen, Qianling; Wang, Benfei
With advantage of dealing with various nonlinear system, model predictive control (MPC) strategy has been applied commonly in power system, however, there is a large computation burden in the traditional MPC strategy. To overcome the shortcoming of MPC, this paper implements event triggered model predictive control (ET-MPC) strategy in grid-connected microgrid system (GMS), which activates MPC once the triggered condition is satisfied; otherwise MPC operation will be stopped. Therefore, it helps to reduce online calculation amount and switching action greatly. To verify the feasibility and superiority of the proposed ET-MPC strategy applied in GMS, the corresponding simulation studies have been conducted in Matlab/Simulink. The various simulation and comparison results, demonstrate the effectiveness of proposed ET-MPC strategy for the GMS.